The histone variant h3.3 marks active chromatin by replication-independent nucleosome assembly. - Ahmad, K.; Henikoff, S. (Molecular Cell, 2002)
Two very similar H3 histones-differing at only four amino acid positions-are produced in Drosophila cells. Here we describe a mechanism of chromatin regulation whereby the variant H3.3 is deposited at particular loci, including active rDNA arrays. While the major H3 is incorporated strictly during DNA replication, amino acid changes toward H3.3 allow replication-independent (RI) deposition. In contrast to replication-coupled (RC) deposition, RI deposition does not require the N-terminal tail. H3.3 is the exclusive substrate for RI deposition, and its counterpart is the only substrate retained in yeast. RI substitution of H3.3 provides a mechanism for the immediate activation of genes that are silenced by histone modification. Inheritance of newly deposited nucleosomes may then mark sites as active loci.